Підходи до визначення сутності необоротних активів підприємства та шляхи поліпшення їх використання - Колосок, Андрій Мирославович; Петрук, Олена Миколаїівна (ОНУ імені І. І. Мечнікова, 2016)
В статті розглянуто сутність та значення необоротних активів в сучасних умовах діяльності підприємства. Досліджено показники, за допомогою яких визначають ефективність їх використання. Здійснено аналіз необоротних активів на прикладі ПАТ «Електротермометрія» та розглянуто можливості покращення їх використання. Ключові слова: необоротні активи, майнові цінності, основні засоби.
In the article the essence and value of fixed assets in the current circumstances of the company in terms of various scientists. Investigated separation performance using non-current assets Pokropyvnym S. F., Bondar N. M. and Sidun V. A. , and the main of them using the enterprise. The analysis of non-current assets on the example of JSC "Elektrotermometriya" and discussed the possibility of improving their use. We believe to fixed assets include assets used for a long period of time, from which the company hopes in the future to benefit and their cost can be reliably measured. Was concluded that there is no consensus on the nature of fixed assets. Scientists are divided into two groups. Some believe that the current assets of the enterprise value of the property, and others that are tangible and intangible resources. Although scientists are divided differently performance using non-current assets exist only system of key indicators of the group. In our opinion they are also to be added rate of depreciation of fixed assets and the production rate of return of intangible assets. To improve the efficiency of fixed assets the company must: optimize the structure of existing equipment, eliminate equipment that is not used to provide further intensification of production processes. To reduce the loss of fixed assets and maintain their financial stability should improve the utilization of production capacity, taking into account their deterioration. As a result of this study was relatively approaches to the selection of indicators to measure the efficiency of fixed assets improving the efficiency of methods of analysis of fixed assets, intangible assets dynamics found and identified areas for improvement in their use of PJSC "Elektrotermometriya." Keywords: non-current assets, property holdings, fixed assets.
Keywords: необоротні активи; основні засоби; майнові цінності; 658.274